USING GIS AND EARTHQUAKE SCENARIOS FOR THE ASSESSMENT OF EMERGENCY RESPONSE IN CASE OF A STRONG EARTHQUAKE. AN APPLICATION IN THE URBAN AREA OF THESSALONIKI, GREECE - Stratou, M.; Savvaidis, A.; Papadopoulou, M.; Panagiotopoulos, D. G. (Bulletin of the Geological Society of Greece, 2004)
The aim of this paper, which is part of the M.Sc Thesis of the first author, is an initial attempt for the assessment of the emergency response through the road network of the Urban Area of Thessaloniki (UAT) after a strong earthquake. The areas of the road network that are to become inaccessible either due to partial collapse of buildings or due to destruction of the road axes by rupture zones, are detected. The inaccessible parts are determined for the cases of three earthquake scenarios using the values of the Peak Ground Acceleration (PGA), which were calculated for about 6000 points over the UAT, as well as spatial overlay tools of a GIS. In the end, by applying network analysis and according to the situation of the network after the earthquake, the possibility of movement of the fire engines and ambulances was studied and least cost routes from ambulance stations to UAT hospitals were tracked.